Liberalizing basic telecommunications: The Asian experience - Carsten Fink; Aaditya Mattoo; Randeep Rathindran (Hamburg Institute of International Economics (HWWA), 2002)
The liberalization of the basic telecommunications sector in Asian countries is examined in this paper with a view to identify the elements of good policy and examine how it can be promoted through multilateral negotiations. We find that despite the move away from traditional public monopolies, most Asian governments are still unwilling to allow unrestricted entry, eliminate limits on private and foreign ownership, and establish strong independent regulators. Where comprehensive reform including privatization, competition and regulation has been implemented, there are significantly higher levels of main line availability, service quality and labor productivity. Somewhat surprisingly, there has not been much unilateral liberalization since the last round of GATS telecommunications negotiations. The new round therefore faces the challenge of not merely harvesting unilateral liberalization as in the past, but of negotiating away existing restrictions. Furthermore, since quantitative restrictions on the number of suppliers are pervasive, deepened GATS rules could help ensure the transparent and non-discriminatory allocation of licenses. There may also be a need to sharpen the regulatory principles established in the last round, and to create rules that safeguard not only the rights of foreign suppliers but also those of consumers. – – In diesem Papier wird die Liberalisierung des Telekommunikationssektors in asiatischen Ländern mit dem Ziel untersucht, die Elemente guter Politik zu identifizieren und zu prüfen, wie diese Politik durch multilaterale Verhandlungen unterstützt werden kann. Trotz ihrer Abkehr von traditionellen staatlichen Monopolen sind die meisten asiatischen Regierungen weiterhin nicht geneigt, uneingeschränkten Marktzugang zu gewähren, Beschränkungen privaten und ausländischen Eigentums an Telekommunikationsunternehmen aufzuheben und starke unabhängige Regulierungsbehörden zu schaffen. Wir zeigen, dass dort, wo umfassende Reformen - Privatisierung, Wettbewerb und Regulierung - durchgeführt wurden, die Zahl der Anschlüsse, die Servicequalität und die Arbeitsproduktivität deutlich gestiegen sind. Etwas überraschend ist, dass es seit der letzten Runde der Telekommunikations-verhandlungen unter dem GATS (General Agreement on Trade in Services) kaum einseitige Liberalisierungen gegeben hat. Die neue Runde steht deshalb vor der Aufgabe, nicht nur - wie in der Vergangenheit - einseitige Liberalisierungen zu ,,ernten“, sondern existierende Beschränkungen in Verhandlungen zu beseitigen. Da die Zahl der Anbieter regelmäßig begrenzt ist, könnten vertiefte GATS-Regeln überdies dazu beitragen, die transparente und nicht-diskriminierende Zuteilung von Lizenzen zu gewährleisten. Außerdem könnte es notwendig sein, die in der letzten Runde beschlossenen Regulierungsgrundsätze zu schärfen und Regeln festzulegen, die nicht nur die Rechte ausländischer Anbieter sondern auch die der Verbraucher sichern.
Keywords: F13; L96; F02; 330; International Economic Order; Trade Negotiations; Market Liberalization; Services Trade; Telecommunication Services; Telekommunikation; Deregulierung; Internationaler Dienstleistungsverkehr; WTO-Regeln; Asien